Validation of an in house iELISA for serodiagnosis of caprine brucellosis and evaluation of the performance of a B. neotomae lysate for the detection of anti-smooth Brucella specific antibodies in ruminants - Foster, Camila Nayla; Rossi, Ursula Amaranta; Rossetti, Carlos Alberto (Elsevier, 2025)
Enzyme-linked immunosorbent assay (ELISA) is a widely used and effective tool for detection of anti-Brucella antibodies in serum, easy to perform with high sensitivity and specificity. In this study, we validated an in-house indirect ELISA using B. melitensis whole cell lysate as antigen (Bm-WCL iELISA) for the serodiagnosis of caprine brucellosis and evaluated the use of BSL-2 B. neotomae in replacement of BSL-3 Brucella species as an antigen for the detection of Brucella-specific antibodies in ruminant sera. Using 724 serum samples from female crossbred goats classified as brucellosis-positive or -negative by both the buffered plate antigen (BPA) and the complement fixation (CF) tests, the Bm-WCL iELISA was successfully validated with a sensitivity (Se) of 91.83 % (88.51–94.25 %) and a specificity (Sp) of 97.41 % (95.41–98.70 %). In addition, the Bm-WCL iELISA showed a great concordance with a commercial iELISA kit (k = 0.94) in a subset of 217 serum samples. To avoid working with a BSL-3 Brucella for antigen preparation, we replaced it with a less virulent Brucella species such as B. neotomae. A total of 214 goat and 220 cow serum samples were evaluated for the diagnosis of brucellosis using the B. neotomae whole cell homogenate (Bn-WCL) iELISA. The analysis of the ROC curves suggested cut-off values of 63.83 PP for goats and 24.04 PP for cattle, with associated Se and Sp of 98.18 % (93.61–99.68 %) and 90.38 % (83.20–94.69 %) respectively in goat sera, and 95.45 % (89.80–98.04 %) and 96.36 % (91.02–98.58 %) of Se and Sp, respectively in cattle. These results confirm the utility of the in house Bm-WCL iELISA and encourage validation of the Bn-WCL iELISA for the serodiagnosis of ruminant brucellosis in resource-limited areas where the disease is endemic.